Micro Novels: New Teaching Materials for MTI’s Literary Translation Course - gang (Pacific International Journal, 2024)
The mainstream literary style of Chinese literature and even the world literature is the novel. The main literary style involved in MTI literary translation course is the novel. Among them, the micro novel is short in form, broad in content and close to the times, which conforms to the teaching goal of MTI literary translation course and students’-“vision of expectation”. This paper discusses the necessity and feasibility of using micro novels as new teaching materials in MTI literary translation course, so as to provide reference for guiding the current teaching of MTI literature course.